Economic Perspectives of the Inaugural Speeches of Barack Obama and Donald Trump - Budhathoki, Krishna Hari (Economic Journal of Nepal, 2023)
Barack Obama and Donald Trump, former presidents of the U.S.A., played a crucial role in driving economic development through their inaugural addresses and public communication. By articulating development agendas and fostering public support through their speeches, they create a conducive environment for policy approval and implementation. They set the tone for the development agenda, emphasizing key priorities and outlining strategies for achieving them. Their speeches serve as primary instruments for conveying development visions, inspiring collective actions, and identifying gaps in economic progress to meet the set goals. Hence, the major aim of the paper is to comprehensively examine the relationship between leadership rhetoric and economic development by employing a mixed-methods approach combining thematic, descriptive, and quantitative analyses. The findings elucidate the interplay among leadership rhetoric, policy implementation, and economic outcomes, giving more priority to economic stability, sustainable growth, and broad-based prosperity despite rhetorical differences. The study concludes that there are valuable insights into leadership roles in economic development. Hence, leaders play a big role in economic development. Adapting these lessons can help various nations like Nepal to achieve sustainable development and improve the well-being of their citizens.